Study of The Effect of Boswellia Leaf Extract on The Activity of Cardiac Enzymes (ALP, AST, ALT, LDH) Using Spectroscopic Methods - Aseel Khalil Ibraheem; Heyam A. Hashim; Shaymaa Saadi Abbood (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of Boswellia carterii leaf extracts on serum enzyme activity in myocardial infarction (MI) patients. Employing a comparative analysis between 60 healthy individuals and 40 cardiac patients, we measured the serum activity of ALP, AST, ALT, and LDH enzymes. Our findings reveal elevated enzyme activity in MI patients. We explored the inhibitory effects of aqueous, alcoholic, and ethyl acetate extracts of Boswellia carterii on these enzymes, demonstrating non-competitive inhibition. The inhibition ratio of ALT, ALP, and AST post-treatment was quantitatively assessed. Statistical analysis was conducted using SPSS-26 with independent t-tests. This research highlights the potential therapeutic role of Boswellia carterii in modulating enzyme activity associated with cardiac events, suggesting avenues for novel treatments in cardiac care.